A preliminary study on the neurocognitive deficits associated with loneliness in young adults - Jin, Eunju; Hwang, Samuel Suk-Hyun (Frontiers in Public Health, 2024)
The experience of loneliness is universal and may have an adverse effect on neurocognitive functioning even at a younger age. Using a comprehensive neurocognitive functioning test (NCFT) battery, we examined the possible negative effects of loneliness on neurocognitive functioning in young adults. The high-loneliness and low-loneliness groups were screened using the UCLA Loneliness Scale v. 3, and measures pertaining to the domains of intelligence, attention, memory, executive function, and psychomotor functioning were tested and compared. As depression and anxiety were significantly higher in the high-loneliness group, an analysis of covariance was conducted. As a result, the high-loneliness group showed significantly poor performance on measures of executive function and attention prior to controlling for depression and anxiety, and executive function retained its significance even after controlling for these variables. Additional analysis showed that depression and anxiety did not significantly mediate the relationship between loneliness and neurocognitive functioning. Such results suggest that loneliness is likely to negatively affect executive functioning and attention in early adulthood and then progressively spread to other domains of cognitive functioning, as reported in the older adult population. The limitations and implications of the present study were considered and addressed.